Towards Elucidating the Rotary Mechanism of the Archaellum Machinery - Nuno de Sousa Machado, João; Albers, Sonja-Verena; Daum, Bertram (Frontiers in Microbiology, 2022)
Motile archaea are able to swim by means of a molecular machine called archaellum. This structure consists of a filament attached to a membrane-embedded motor. The archaellum is found exclusively in members of the archaeal domain, but the core of its motor shares homologues with the motor of type IV pili (T4P). Here we provide an overview of the different components of the archaellum machinery and provide hypothetical models to explain how rotary motion of the filament is powered by the archaellum motor.